(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Handwriting Analysis is described as a scientific study for the analysis of handwriting. It is a way of interpreting and ability to learn from peculiarities in handwriting. Offline handwriting analysis is a traditional approach that cannot be used efficiently for analysis. Online handwriting analysis, on the other hand, can utilize various aspects like pressure on the pen, timestamp and other factors which help in improving the effectiveness of analysis. Learning disabilities are neurological processing problems which can hamper the learning of the children. Dysgraphia is a learning disability that mainly affects a child’s handwriting and motor skills. It is found in 10 to 30% of school-aged children. Dysgraphia can be diagnosed by therapists based on children’s handwriting samples and manual evaluation techniques. This method is lengthy and inaccurate. In this work, automatic identification methods for and classification of dysgraphia in children in the age group 7 to 12 is described. The method performs analyzing of the child’s writing dynamics via blueprints of the pressure the pen puts on paper with the pen’s movements and orientation with the use of a standardized digital writing pad and machine learning algorithms. It basically has two phases, the training phase, and testing phase. In the training phase, handwriting samples of known results are given to the system. Then the model is built using some classifier, Random forest or Support Vector Machine. Once the model is trained, then in testing phase this model is used for classification of unknown samples to predict whether the subject has dysgraphia or not. This is then used to check the accuracy of the designed system.